2004
DOI: 10.1016/j.jasms.2003.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Q-trap mass spectrometer, a novel tool in the study of protein glycosylation

Abstract: The use of the recently introduced Q-Trap mass spectrometer in the study of protein glycosylation is described. The combined ion trap and triple quadrupole scan functions make it a powerful system in both oligosaccharide and glycopeptide analysis. Several oligosaccharides, both linear and branched, were analyzed to obtain information on sequence, linkage, and branching. Quadrupole like MS/MS spectra with ion trap sensitivity but without the typical ion trap low mass cut-off were obtained. To determine the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…Early work using collision-induced dissociation (CID) 1 has identified a few key features that are characteristics of the fragmentation of glycopeptides, providing the basis for intact glycopeptide identification (75)(76)(77)(78)(79). The analysis of intact glycopeptides has been carried out using a variety of different instruments, including electrospray ionization (EST)-based ion trap (IT) (80 -84), quadrupole ion trap (QIT) (85)(86)(87), Fourier transform ion cyclotron resonance (FTICR) (31, 57, 88, 89), ion trap/time-of-flight (IT/TOF) (90,91), and quadrupole/time-of-flight (Q/TOF) (92-97); matrix-assisted laser desorption/ionization (MALDI) based Q/TOF (98 -100), 1 The abbreviations used are: CID, collision-induced dissociation; Q, quadrupole.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early work using collision-induced dissociation (CID) 1 has identified a few key features that are characteristics of the fragmentation of glycopeptides, providing the basis for intact glycopeptide identification (75)(76)(77)(78)(79). The analysis of intact glycopeptides has been carried out using a variety of different instruments, including electrospray ionization (EST)-based ion trap (IT) (80 -84), quadrupole ion trap (QIT) (85)(86)(87), Fourier transform ion cyclotron resonance (FTICR) (31, 57, 88, 89), ion trap/time-of-flight (IT/TOF) (90,91), and quadrupole/time-of-flight (Q/TOF) (92-97); matrix-assisted laser desorption/ionization (MALDI) based Q/TOF (98 -100), 1 The abbreviations used are: CID, collision-induced dissociation; Q, quadrupole.…”
mentioning
confidence: 99%
“…More details regarding mass spectrometric analysis of intact glycopeptides can be found in recent reviews (56,124). Although great efforts have been made to apply a variety of mass spectrometry techniques to study both N-linked (32, 56,86,87,[112][113][114][125][126][127][128][129][130] and O-linked (90, 116, 119, 120, 130 -140) glycopeptides, the interpretation of the fragment spectrum of an intact glycopeptide still requires intensive manual assignment and evaluation. A recent study has demonstrated the feasibility to develop an automated workflow for analyzing intact glycopeptides in mixtures (141).…”
mentioning
confidence: 99%
“…Protein glycosylation is of particular interest since it is the most common protein modification [1][2][3][4][5]. Glycosylation plays a crucial role not only in protein structure but also in cell-cell recognition, and perhaps even signaling mechanisms [6 -8].…”
mentioning
confidence: 99%
“…In recent studies, LC/MS has frequently been employed for peptide mapping. The MS-based peptide mapping of proteolytic glycoproteins enables not only the analysis of amino acid sequences but also the detection of site-speciˆc glycosylation (7)(8)(9)(10). As an example of peptide mapping, here, we describe the MS-based peptide mapping that has previously been performed for tissueplasminogen activator (t-PA) (11), which is an anticoagulant, and for a monoclonal antibody (12).…”
Section: B Lc/ms Of Proteolytic Glycoproteinsmentioning
confidence: 99%